Fabrication of Dye-Sensitized Solar Cells with a 3D Nanostructured Electrode - Guo-Yang Chen; Ming-Way Lee; Gou-Jen Wang (International Journal of Photoenergy)
A novel Dye-Sensitized Solar Cell (DSSC) scheme for better solar conversion efficiency is proposed. The distinctive characteristic of this novel scheme is that the conventional thin film electrode is replaced by a 3D nanostructured indium tin oxide (ITO) electrode, which was fabricated using RF magnetron sputtering with an anodic aluminum oxide (AAO) template. The template was prepared by immersing the barrier-layer side of an AAO film into a 30 wt% phosphoric acid solution to produce a contrasting surface. RF magnetron sputtering was then used to deposit a 3D nanostructured ITO thin film on the template. The crystallinity and conductivity of the 3D ITO films were further enhanced by annealing. Titanium dioxide nanoparticles were electrophoretically deposited on the 3D ITO film after which the proposed DSSC was formed by filling vacant spaces in the 3D nanostructured ITO electrode with dye. The measured solar conversion efficiency of the device was 0.125%. It presents a 5-fold improvement over that of conventional spin-coated TiO2 film electrode DSSCs.